East Asia and Pacific Update, April 2008 : East Asia - Testing Times Ahead - World Bank (World Bank, Washington, DC, 2020)
Last year Developing East Asia recorded its highest growth rate in over a decade (10.2 percent), capping a decade of improvements following its home-grown financial crisis in 1998. Yet this is hardly a time for celebration, but rather one for concern. The global economy is once again facing a testing time, with soaring fuel and food prices, on the one hand, and, on the other, an unfolding sub-prime crisis emanating in the United States and spreading to other countries and asset classes, bringing in its wake a plunging dollar and a slowdown in global trade and growth. Despite falling growth in exports to the US, rising volatility in global financial markets, high and volatile international commodity prices, and an increasingly clouded outlook for the world economy, economic activity in most East Asian economies continued at strong rates through the end of 2007 and into early 2008. Fortunately, the countries of East Asia are generally better prepared than ever to deal with the vicissitudes of the global economy in this more uncertain time. Reflecting lessons learned from the East Asian financial crisis of a decade ago, today most economies in the region have strong external payments positions and large international reserves, prudent fiscal and monetary policies, better regulated banking systems, and profitable and competitive corporations. East Asia's trade and financial relations with the rest of the world have become steadily more diverse. The region is becoming more of a growth pole in the world economy, proving to be a force for stability at a time when the industrial economies are slowing.